2010
DOI: 10.1111/j.1365-2672.2010.04722.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of type III secretion systems in Vibrio parahaemolyticus from the northern Gulf of Mexico

Abstract: Aims:  Two well‐characterized Vibrio parahaemolyticus pathogenicity factors – thermostable direct haemolysin (TDH) and TDH‐related haemolysin – are produced by strains containing the tdh and trh genes, respectively. Most strains of V. parahaemolyticus contain two nonredundant type III secretion systems (T3SS), T3SS1 and T3SS2, both of which contribute to pathogenicity. Furthermore, a recent study has revealed two distinct lineages of the V. parahaemolyticus T3SS2: T3SS2α and T3SS2β. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
50
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 32 publications
5
50
3
Order By: Relevance
“…T3SS2 appears to be involved in enterotoxicity in vitro and may play a role in the environmental fitness of strains (14,23,33). All V. parahaemolyticus isolates contain T3SS1 (31,33). Two distinct lineages of T3SS2 have been described, showing correlations of tdh with T3SS2␣ and of trh with T3SS2␤ (31,33).…”
mentioning
confidence: 99%
“…T3SS2 appears to be involved in enterotoxicity in vitro and may play a role in the environmental fitness of strains (14,23,33). All V. parahaemolyticus isolates contain T3SS1 (31,33). Two distinct lineages of T3SS2 have been described, showing correlations of tdh with T3SS2␣ and of trh with T3SS2␤ (31,33).…”
mentioning
confidence: 99%
“…Other studies (19)(20)(21) have reported that the tdh gene is encoded and co-regulated with T3SS2a genes, and that the T3SS2b genes have been detected in trh-positive strains. Moreover, all isolates contain T3SS1 (19,20). Thus, the results of the assays for virulence genes in this study are consistent with those of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…T3SS: We also examined T3SS genes as potential indicators of virulence by PCR assays according to previously published studies (19,21) (Table 1). The targeted genes were VP1670, VP1686, VP1689, and VP1694 as T3SS1 genes, VPA1327, VPA1335, VPA1339, and VPA1362 as T3SS2a genes, and vscS2, vscC2, vopC, and vopB2 as T3SS2b genes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many bacterial pathogens use type III secretion systems (T3SSs) for survival in the host by injecting virulence factors directly into the host. V. parahaemolyticus encodes two T3SSs that exhibit different phenotypes during disease (19)(20)(21). V. parahaemolyticus also exhibits "phase variation" and can switch from an opaque (OP) to a translucent (TR) phenotype based on polysaccharide production (22).…”
mentioning
confidence: 99%